Al-Halu‘ (Kecelaruan Kebimbangan) dan Perbahasannya Serta Hubungannya dengan Psikologi Islam: The Discussion of Al-Halu‘ (Anxiety Disorder) and the Relationship with Islamic Psychology - Sa’ari, Che Zarrina; Syed Muhsin, Sharifah Basirah; Mohd Akib, Mohd Manawi (Jurnal Usuluddin, 2021)
The demands in following the currents of modernization today are a great challenge in human life. The matter also causes various problems, especially psychological problems, one of which is an anxiety disorder. Among Islamic scholars, the disorder is referred to as al-haluʻ which is closely related to one's state of the soul. From the point of view of Western psychology, the discussion about it only stops at the level of theory and experimental results by setting aside the spiritual element as well as revelation (wahy). While from the Islamic psychospiritual point of view, the discussions by scholars have occurred earlier that is since the early days of the spread of Islam and it has been discussed in more detail with a focus on the physical aspects characterized by restless behavior, anxiety, extreme worry, and grievances, in addition, does not set aside the emotional and spiritual aspects which are marked among others by feelings of restlessness, stinginess, and greed. The study employed a qualitative method using a content analysis approach. Data on al-haluʻ were collected through the documentation method and then analyzed utilising thematic descriptive methods. The findings of the study indicate that the Islamic psychospiritual sees the element of the soul (al-nafs) as a key element in discussing the various aspects or dimensions related to this spirituality. This is because the soul greatly influences a person's personality whether good or bad. Thus, al-halu ‘ has been categorized as a mental disorder that requires treatment which is suggested through the approach of purification of the soul (tazkiyah al-nafs) based on the elements of Sufism because the soul is the birthplace of this disorder. Although Western psychologists have also included this problem of anxiety disorder as one of the mental disorders that must be treated and addressed, and there are some aspects of the debate that are seen as similar between Islam and the West, but there is still a huge gap of difference between the two especially in linking this disorder with spiritual aspects and revelation.